ANALYSIS OF THE PERCEPTION INFORMATION METHODICS BY STUDENTS IN THE HIGHER TECHNICAL EDUCATIONAL INSTITUTION - Рахманов, В. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
In the article the methods of information perception are considered. Using mathematical methods of training improves professionals features formation of  the future specialists and confirm the optimality perception of information at each stage of preparation